Challenges in slug modeling and control for offshore oil and gas productions: A review study. (January 2017) - Pedersen, Simon; Durdevic, Petar; Yang, Zhenyu
Abstract: The upstream offshore multi-phase well-pipeline-riser installations are facing huge challenges related to slugging flow: An unstable flow regime where the flow rates, pressures and temperatures oscillate in the multi-phase pipelines. One typical severe slug is induced by vertical wells or risers causing the pressure to build up and hence originates the oscillating pressure and flow. There exist many negative consequences related to the severe slugging flow and thus lots of investments and effort have been put into reducing or completely eliminating the severe slug. This paper reviews in details the state-of-the-art related to analysis, detection, dynamical modeling and elimination of the slug within the offshore oil & gas Exploration and Production (E&P) processes. Modeling of slugging flow has been used to investigate the slug characteristics and for design of anti-slug control as well, however most models require specific facility and operating data which, unfortunately, often is not available from most offshore installations. Anti-slug control have been investigated for several decades in oil & gas industry, but many of these existing methods suffer the consequent risk of simultaneously reducing the oil & gas production. This paper concludes that slug is a well defined phenomenon, but even though it has been investigated for several decades the current anti-slug control methods still have problems related to robustness. It is predicted that slug-induced challenges will be even more severe as a consequence of the longer vertical risers caused by deep-water E&P in the future.